Occurrence of Ascaridia galli and Heterakis gallinarum in Guinea Fowl (Numida meleagris) in the State of Rondônia, Brazil - Boroviec, Brunas Bastos; Gilio Gasparotto, Paulo Henrique; Dantas Filho, Jeronimo Vieira; Mesquita Peixoto, Renato; Almeida Viana, Geysa; Coutinho Marques Rocha, Ana Sabrina; Daudt, Cíntia; Chaves da Silva, Flavio Roberto (Acta Scientiae Veterinariae, 2020)
Background: Parasitic diseases are among the problems that most affect birds. The Ascaridia spp. is one of the genera which is responsible for the main infections, and the Ascaridia. galli is the most frequent species found in birds. The Ascaridia spp. egg is oval and present a smooth shell which could be mistaken with the Heterakis gallinarum eggs, once they are the most frequent parasites in birds. Therefore, this case report describes the occurrence of Ascaridia galli and Heterakis gallinarum in a guinea fowl (Numida meleagris) feces and gut. Case: In January 2017, rain season in northern Brazil, a visit was performed to a free range avian breeding property in the municipality of São Miguel do Guaporé in the state of Rondônia, Brazilian Amazonian Region. The property breeds two chicken species: Gallus gallus domesticus and Numida meleagris as well as one quail species. The problem was related to the guinea fowl breeding which was composed by 50 adults and 45 young birds about two or three weeks old. All 45 young guinea fowl were presenting various clinical signs, which included: yellowish catarrhal diarrhea, isolation, loss of appetite, body weight, ruffled feathers, drooping wings and sternal prominence. All animals that presented the clinical signs as ruffled feathers, drooping wings and sternal prominence died on an average of 24 h and the mortality was of 65.9% (29/45). Subsequently, a three-week old bird corpse was necropsied, and it was observed that its intestines presented a large amount of endoparasites besides presenting thickening. As there were a lot of helminths, they were collected along with the intestinal content for examination. The parasitological examinations of the feces were performed by Willys Molay’s technique. As a result of the fluctuation technique, were observed and identified large quantities of Heterakis gallinarum and Ascaridia galli eggs. The adult worms of H. gallinarum and A. galli were identified using dichotomous key. Discussion: Ascaridia galli and Heterakis gallinarum infection were reported in guinea fowl in a free range chicken breeding property in the municipality of São Miguel do Guaporé in the state of Rondônia, Brazilian Amazonian Region. Ascaridia galli and Heterakis gallinarum eggs have already been identified in free-range chickens (Gallus gallus domesticus) by flotation techniques, as Willys Mollay and Faust and they are the main species of helminths housed by chickens. However, these parasites are not commonly reported in guinea fowl worldwide, especially in the Numida meleagris species. Regarding necropsy, intestinal wall thickening is generally a common finding which has been reported in chickens, however it is not commonly reported in guinea fowl. Additionally, the presence of clinical signs of nematode parasitosis frequently occurs in birds with high parasitic load. In this report, we believe that the guinea fowls births on the rain season was one of the factors to the high parasites incidence found, since both nematodes species are frequently identified in the rain seasons. Additionally, the management adopted by the breeder, using concomitantly the same nursery for guinea fowl and chicken, added up to inadequate sanitary management, seems to have directly influenced the contamination and recontamination of the different brood litter of guinea fowls. It is concluded that guinea fowl (Numida meleagris) located in the state of Rondônia were affected by high amounts of Ascaridia galli and Heterakis gallinarum and caused high mortality in the young specimens and consequently causing economic losses to the proprietary.